INCLUSIVE EDUCATION FOR STUDENTS WITH BLIND DISABILITIES IN THE LIBRARY SCIENCE STUDY PROGRAM UIN JAKARTA - Fadhilatul Hamdani (JURNAL ILMU PERPUSTAKAAN (JIPER), 2024)
This study analyzes the implementation of inclusive education for blind students in the Library Science Study Program, Faculty of Adab and Humanities, UIN Syarif Hidayatullah Jakarta. A qualitative descriptive method with a case study approach was used, involving interviews, observations, and documentation. The selection of informants used a purposive sampling technique, namely, the head of the study program and several lecturers who had taught courses in inclusive classes. Triangulating sources carried out data validity testing. The study results showed that lecturers understand the concept of inclusive education but do not understand the specific needs of blind students. Study programs and lecturers are not fully ready to implement inclusive education due to the absence of standards and technical guidelines. Teaching activities are carried out based on the understanding of each lecturer. Various obstacles were identified in this study, ranging from inadequate facilities for blind students that have not been properly accommodated by the campus to the absence of training or technical guidance for lecturers in preparing themselves to teach in inclusive classes, to the lack of motivation for blind students with special needs in lectures. The suggestion from this study is that a policy should be established regarding lecture activities for students with special needs, particularly those who are blind. This research implies that there must be improvements in clear policies and guidelines, strengthening of human resources, preparation of supporting facilities and infrastructure, increasing campus awareness and sensitivity, and ongoing evaluation and supervision.